Dampak Meme Anomali Brainrot Pada Pemerolehan Kosakata Gen-Alpha: Studi Kajian Psikolinguistik - Azizah, Fauziyah; Saputra, Kaman Jaya; Tisnasari, Sundawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the impact of Brainrot memes on Generation Alpha's vocabulary development from a psycholinguistic perspective. Qualitative methods were used through semi-structured interviews with 7-10 year old children and parents. Results show that Brainrot memes introduce new vocabulary significantly through digital platforms. Children can adopt the absurd words in their daily communication. However, there are also negative effects such as difficulty in choosing the right language register and a tendency to think less critically. In conclusion, although Brainrot memes can enrich vocabulary, overexposure has the potential to hinder the formation of a productive mental lexicon. The need for parental supervision of digital content and strengthening language learning in structured contexts is suggested.